1994
DOI: 10.1088/0268-1242/9/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of light emission from silicon devices

Abstract: The fundamentals of light-emitting phenomena from silicon semiconducting material are presented from an experimental rather than a theoretical point of view. The following aspects are considered in detail. In the first place, laterally resolved measurements give information about the distribution of emitted light, which has been generated by an excited radiative system. Secondly, spectrally resolved experiments enable a distinction to be made between different current transport mechanisms and permit discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 59 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…Since the spectra of all breakdown types are very similar to avalanche breakdown spectra in the literature 13,14 and in Ref. 25 tunneling breakdown is demonstrated to emit no photons, we conclude that avalanche breakdown is mainly responsible for the reverse EL at all breakdown sites independently of their type.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Since the spectra of all breakdown types are very similar to avalanche breakdown spectra in the literature 13,14 and in Ref. 25 tunneling breakdown is demonstrated to emit no photons, we conclude that avalanche breakdown is mainly responsible for the reverse EL at all breakdown sites independently of their type.…”
Section: Discussionsupporting
confidence: 80%
“…13, an increase in the diameter of the breakdown site with increasing voltage was predicted due to a spreading of the charge carriers. We verify this effect and show that the diameter of this breakdown site is about 0.5 m ͓Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Subsequent work [22] with devices where a high electric field could be obtained, as well as using punch through devices not in avalanche, indicated that the high energy emission spectrum is electron dominated, thus favoring indirect interband hot electron and hole (c-v) recombination or hot electron intraband transitions (c-c) as the dominant processes for the higher photon energies.…”
Section: A Early Observationsmentioning
confidence: 99%
“…Low temperature electro-and photoluminescence has been since a long time a standard tool for silicon defect characterization, but nowadays there is again a strong interest in crystalline silicon electroluminescence at room temperature mainly in two fields: First of all the silicon photonics community is still looking for an efficient emitter [7] and high efficient silicon homojunction solar cells [8] and amorphous silicon on crystalline silicon heterojunction solar cells [9] have also been demonstrated to have for some applications acceptable values of the emitted power at infrared wavelengths. Regarding the solar cell production, there is a strong need for noninvasive, low-cost and fast production monitoring tools.…”
Section: Introductionmentioning
confidence: 99%